Desain LKPD Fisika Terintegrasi HOTS Untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Asmia Fransiska; Erwin Prasetyo; Adi Jufriansah (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2021)
The 2013 curriculum is oriented to the development of the 21st century which is faced with various challenges in the world of education. Things that cause problems in implementing the 2013 curriculum are teacher competencies that are still lacking, online learning facilities are not evenly distributed, and the division of learning hours using a shift system causes the quality of students and education itself to be lacking. This study aims to provide solutions to problems faced in schools, namely by developing HOTS integrated worksheets to improve students' critical thinking skills. This type of research is development (R&D) which refers to the 4-D model, namely define, design, develop, disseminate. The feasibility of the HOTS integrated LKPD media was obtained from the results of expert validation, LKPD media trials in the form of practicality analysis and effectiveness analysis. The improvement of students' critical thinking skills is obtained from the standard value of the N-gain test of students' critical thinking abilities. The results of the study indicate that the HOTS integrated LKPD has been produced which is suitable to be used to improve students' critical thinking skills with a standard N-gain value of 0.71 in the high category.ÃÂ